Association Between IBD Disability and Reduced Work Productivity (Presenteeism): A Population-Based Study in Manitoba, Canada. Issue 2 (10th July 2018) - Shafer, Leigh Ann; Walker, John R; Restall, Gayle; Chhibba, Tarun; Ivekovic, Meloney; Singh, Harminder; Targownik, Laura E; Bernstein, Charles N
Abstract: Background: One effect of IBD disability is reduced productivity when at work (presenteeism). We explored potential predictors of work presenteeism and compared the predictive ability of the recently developed IBD Disability Index (IBDDI) with 4 other scales in predicting presenteeism. Methods: Participants (aged 18–65 years) were recruited from the University of Manitoba IBD Research Registry. We calculated a presenteeism score (range, 0–24) from the Stanford Presenteeism Scale (SPS), with higher scores representing greater degrees of presenteeism. Using receiver operating characteristic curves and linear regression, we explored associations between presenteeism and the IBDDI, the World Health Organization Disability Assessment Schedule (WHODAS 2.0), the Work and Social Adjustment Scale (WSAS), the Inflammatory Bowel Disease Questionnaire (IBDQ), and the Kessler-6 (K6) distress scale. Results: Out of 744 respondents working at least half-time (20+ hours/wk), 472 (63%) reported no reduced productivity in the previous 14 days. Reduced productivity was reported for 1–2 days by 131 (18%), for 3–9 days by 119 (16%), and on most days by 22 (3%). When predicting the SPS, similar model fits were found for the IBDDI, WHODAS, WSAS, IBDQ, and K6. Each increase of 10 on the IBDDI score was associated with an increase of 2.19 (95% confidence interval, 2.00–2.37) on the SPS. Each additional year of disease duration was associated with a reduction in SPS score of 0.08 ( P < 0.01). Conclusions: More than one-third of persons with IBD report presenteeism. We found strong associations between presenteeism and disability, lower quality of life, and emotional distress. The IBDDI performs equally as well as the more established scales in predicting presenteeism.